Using automated writing evaluation in developing ESL learners’ writing proficiency - Abd Razak, Harniza; Lotfie, Maskanah Mohammad; Shah, Mohamed Ismail Ahamad (2018)
This paper presents a study that aims to find possible means in increasing learners’ proficiency level as those who are proficient in English are likely to have better employment and opportunities in the global arena. In particular, the study investigates the use of Automated Writing Evaluation (AWE) applications in facilitating writing competence among English for a Second Language (ESL) learners. The investigation employed WriteLab, a technology-enabled innovation feedback tool which could contribute to developing English language proficiency of students through raising grammatical sensitivity and lexical development. This study has adopted a quasi-experimental design and it involved ESL students from Universiti Teknologi Mara Terengganu (n=80) who were enrolled in a writing course namely Integrated Language Skills: Writing. Based on the content analysis of grammatical sensitivity and lexical analyses conducted by using Measure of Textual Lexical Diversity (MTLD), Latent Semantic Analyses (LSA) and Academic Word List (AWL) with the aid of Co-Metrix 3.0 and Vocabprofiler BNC, results show that grammatical sensitivity and lexical diversity increased among 40 participants who received the treatment using AWE in performing writing tasks. The paper also presents the potentials and the implications of the use AWE in ESL writing courses.